First record of the weevil Otiorhynchus armadillo (Coleoptera:Curculionidae) in Greece - Mpamnaras, Athanasios; Eliopoulos, Panagiotis (ENTOMOLOGIA HELLENICA, 2018)
An entimine weevil is recorded for the first time in Greece. Around the year 2000, Otiorhynchus armadillo (Rossi, 1792) was found in the district of Larisa. Images of the species (of the original specimen collected in Greece) and information on its distribution, ecology and biology, are presented.